CTIM-26. PATIENT-SPECIFIC DENDRITIC CELL VACCINE (DC-ATA) PULSED WITH ANTIGENS FROM SELF-RENEWING AUTOLOGOUS TUMOR CELLS IN THE TREATMENT OF NEWLY-DIAGNOSED GLIOBLASTOMA: A PHASE II TRIAL. (9th November 2020) - Bota, Daniela; Piccioni, David; LaRocca, R; Duma, Christopher; Kesari, Santosh; Carrillo, Jose; O'Donnell, Robert T; Aiken, Robert; Hsu, Frank; Kong, Xiao-Tang; Hsieh, Candace; Langford, Chris; et al.
Abstract: GBM standard treatment is associated with poor survival. Adjunctive therapy with patient-specific vaccines may improve outcomes by enhancing anti-GBM immune responses. A multi-institutional phase II clinical trial was designed with a primary objective of 75% survival 15 months after intent-to-treat enrollment. IL-4 and GM-CSF were used to generate dendritic cells (DC) from monocytes. DC were incubated with autologous tumor antigens (ATA) from the lysate of cultured GBM cells to produce each patient-specific DC-ATA vaccine. Each dose was admixed with 500 mcg GM-CSF at the time of subcutaneous injections at weeks 1, 2, 3, 8, 12, 16, 20 and 24. Enrollment has been completed in April 2020 (n=60). Three patients withdrew from the study prior to starting treatment leaving 57 patients for whom data is available. So far 57 patients have received 344 doses; 27 have completed all 8 doses, 11 received fewer than 8 doses at the time they discontinued treatment, 19 are currently in treatment. No patient has discontinued treatment because of toxicity. 9 pt had died and the preliminary 12 months overall survival is 74%. In a preliminary serologic analysis 12 of 16 patients (75%) had an increase in markers associated with Th1/NK, Th2/immunoglobulins, and Th2 hypersensitivity (eotaxins, IgE and IL17F) by week-3; 9 of 15 (60%) had a decrease in angiogenesis factors, growth factors, and tumor markers by week-8. Immunologic data for all 55 patients who received at least two injections will be available November 2020. This patient-specific DC-ATA immunotherapy approach is feasible, is associated with changes in serologic markers, and may be increasing intratumor inflammation that may be associated with on-target toxicity and efficacy. A interim survival analysis will be conducted in mid-October 2020, 15 months after the 28 th patient was enrolled; results will be available November 2020 [Clinicaltrials.gov NCT03400917].